1995
DOI: 10.1002/jbmr.5650101110
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of bone morphogenetic protein-2 on osteoclast-like cell formation and bone-resorbing activity

Abstract: Although the action of bone morphogenetic protein (BMP) on osteoblast differentiation has been extensively investigated, its effect on osteoclast differentiation remains unknown. In the present study, in vitro effects of BMP-2 on osteoclast-like cell formation and bone resorption were examined. BMP-2 (1-100 ng/ml) significantly stimulated bone resorption by preexistent osteoclast-like cells in mouse bone cell cultures containing stromal cells, whereas it did not affect the bone-resorbing activity of isolated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
1
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(116 citation statements)
references
References 40 publications
5
105
1
3
Order By: Relevance
“…The change of some soluble factors in the serum of this patient by glucocorticoid use and immobilization might be responsible for enhancing the level of ALP, OCN and BMP-2 in osteoblast. Furthermore, increased bone resorption indices may be due to BMP-2, stimulation of bone resorption by enhanced osteoclast formation, and osteoclastic activity [14,15]. Okamoto et al [16] reported that mice overexpressing BMP-4 in bone developed severe osteopenia with increased osteoclast number.…”
Section: Discussionmentioning
confidence: 99%
“…The change of some soluble factors in the serum of this patient by glucocorticoid use and immobilization might be responsible for enhancing the level of ALP, OCN and BMP-2 in osteoblast. Furthermore, increased bone resorption indices may be due to BMP-2, stimulation of bone resorption by enhanced osteoclast formation, and osteoclastic activity [14,15]. Okamoto et al [16] reported that mice overexpressing BMP-4 in bone developed severe osteopenia with increased osteoclast number.…”
Section: Discussionmentioning
confidence: 99%
“…BMPs are differentiating paracrine proteins acting on a variety of cells in bone remodeling, not only bone forming cells but also osteoclasts. 6,15 In the chamber, the results of the osteoclast activity can clearly be seen as the ingrowth front sweeps into the dead graft ( Fig. 2A,B).…”
Section: Manipulating Responses In Bone Graft Remodelingmentioning
confidence: 94%
“…However, resorption can also be increased. 6,7 In bone chambers, BMPs increase bone ingrowth rate in nonvital bone grafts, but also cause an almost simultaneous resorption of newly formed bone. 8 The combination of a local bisphosphonate (clodronate) and BMP-7 caused both increased ingrowth and increased bone density in impacted grafts in the bone conduction chamber model.…”
mentioning
confidence: 99%
“…In culture, human monocytes chemotactically respond to BMP4 [87], while BMP7 stimulates the formation of TRAP positive mononuclear cells which, in the presence of 1,25(OH) 2 D 3 , mature and resorb bone [88,89]. BMP2 also mediates the osteoblast-osteoclast interaction, and in the presence of bone marrow stromal cells supports the maturation of mononuclear cells and bone resorption [90,91]. In the presence of inflammation, BMP2 enhances bone resorption via upregulation of COX-2 and RANKL in osteoblasts [92].…”
Section: In the Presence Of Coupled Bone Cells Bmps Stimulate Resorptionmentioning
confidence: 99%